ANALYSIS OF POLITICAL CARTOONS THROUGH A SEMIOTIC SCIENCE APPROACH - Setiawan, Reviliana Al'Fatihah; Hadi, Imron; Setiawan, Wawan (Sekolah Tinggi Bahasa Asing JIA, 2025)
This research aims to analyze the types of signs in political cartoons based on Charles Sanders Peirce's semiotic theory, specifically icons, indices, and symbols. This research employs a descriptive qualitative method, analyzing 12 political cartoons retrieved from the Instagram account @political_cartoon_gallery in June 2025. The results of the research indicate that political cartoons convey social and political criticism through visual signs with deep meanings, such as visual resemblance (icons), cause-and-effect relationships (index), and meanings based on social conventions (symbols). These findings suggest that political cartoons serve as an effective medium for conveying ideological messages and criticism of global issues. This research is expected to contribute to the development of visual semiotics research and enhance public understanding of the hidden meanings in visual media.